Improving Arabic Speaking Skills Through the Implementation of Daily Arabic Expressions in a Language Environment - Irsal Amin; Mahyudin Ritonga; Sylvia Kurnia Ritonga; Ridho Abdul Ali Abbas Riswan (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
Arabic speaking skills (maharah al-kalam) are widely regarded as a primary objective of Arabic language learning, yet they remain one of the most challenging competencies for students to acquire. This study aims to examine the implementation of a daily Arabic expressions program in enhancing students’ maharah al-kalam at Ma'had Darul Ikhlas Padangsidimpuan. A qualitative approach with a case study design was employed. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing through triangulation. The findings indicate that the implementation of daily Arabic expressions significantly enhanced students’ speaking competence, particularly in terms of fluency, self-confidence, and contextual language use. These improvements were supported by integrated language activities, including Shobahul Lughah, Muhadatsah, Muhadharah, Arabic vlog production, and regular Musabaqah Lughawiyah. Nevertheless, the findings also reveal that improvements in speaking fluency were more substantial than gains in grammatical accuracy. Several challenges affected the implementation of the program, including differences in students’ cognitive abilities, varying levels of learner commitment, limited supervision, and institutional support. The study concludes that a language environment enriched with structured daily Arabic expressions provides an effective strategy for developing students’ maharah al-kalam. However, strengthening grammatical instruction, ensuring consistent implementation, and enhancing institutional support are essential for achieving more comprehensive and sustainable speaking competence.